2023
DOI: 10.1186/s12967-023-04097-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of oily fish and nonoily fish intakes with all-cause mortality and cause-specific mortality: a large population-based prospective study

Abstract: Background There are inconsistent results of cohort studies analyzing the association between fish intake and mortality. Objective This study was performed to explore the association of oily fish consumption and nonoily fish consumption with all-cause mortality and cause-specific mortality. Methods A total of 431,062 participants from the UK Biobank who were without cancer or cardiovascular disease (CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Donat-Vargas et al (2020) [ 172 ] reported that 16779 (24.13 %) females and males were died from the total participants of 69497 by a nutritional-toxicological aspect of fish consumption. According to the finding of Zhou et al (2023) [ 173 ], 75574 (17.53 %) of 383248 oily fish consumption and 70092 (16.26 %) of 410499 non-oily fish consumption were died with ≥2serving/week. Wallin et al (2018) [ 174 ] reported, 794(15.56 %) of 5103 female participants were died by coronary heart disease (CHD) and type-2 diabetes case with fish consumption 1–3 servings/month.…”
Section: Mortality Rate Due To Fish Consumptionmentioning
confidence: 99%
“…Donat-Vargas et al (2020) [ 172 ] reported that 16779 (24.13 %) females and males were died from the total participants of 69497 by a nutritional-toxicological aspect of fish consumption. According to the finding of Zhou et al (2023) [ 173 ], 75574 (17.53 %) of 383248 oily fish consumption and 70092 (16.26 %) of 410499 non-oily fish consumption were died with ≥2serving/week. Wallin et al (2018) [ 174 ] reported, 794(15.56 %) of 5103 female participants were died by coronary heart disease (CHD) and type-2 diabetes case with fish consumption 1–3 servings/month.…”
Section: Mortality Rate Due To Fish Consumptionmentioning
confidence: 99%